Detection of Oesophageal Fistula by Radionuclide Salivagram SPECT/CT - Wang, Yingwei; Wang, Chao; Liu, Lin; Huang, Xinwen; Guo, Zhaoyou; Zeng, Wei; Sun, Rui; Chen, Yue (Frontiers in Oncology, 2021)
Purpose Videofluoroscopic swallowing study (VFSS) is currently the most widely used clinical examination method for diagnosis of oesophageal fistula, but it has many limitations. Therefore, we evaluated radionuclide salivagram single-photon emission computed tomography (SPECT/CT) as a new method of oesophageal fistula diagnosis. Methods We retrospectively evaluated the data of 11 patients (10 men and 1 woman, aged 41 to 70 years, with an average age of 58.6 years) who had clinically suspected oesophageal fistula from January 2019 to October 2020. They underwent radionuclide salivagram SPECT/CT and VFSS examinations, and we analysed and compared the results of the two examinations. Results A total of 11 patients were included in this study. Ten underwent both salivagram and VFSS examinations. One patient was unable to swallow the contrast agent; therefore, only salivagram was performed, and we excluded this patient from the VFSS analysis. A total of 11 patients underwent salivagram examinations, of which 6 were positive and 5 were negative. A total of 10 patients were tested by VFSS, of which 6 results were positive and 4 were negative. Conclusion Radionuclide salivagram SPECT/CT and VFSS are complementary, which can greatly improve the clinical diagnosis and prognosis of oesophageal fistula. When the patient cannot perform the VFSS, or the clinical symptoms are inconsistent with the VFSS imaging findings, the salivagram is an ideal test method.